Rancang Bangun Peta Digital Desa di Kaligentong Boyolali Berbasis Web dan Android - Rochmatika, Rizkha Ajeng; Sasono, Sindung Hadwi Widi; Suharjono, Amin; Supriyanto, Eko; Novitasari Mara, Muhlasah; Rochadi, Agus; Hidayah, Nurul; Rohmah, Nuriyana (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
To support the management of large-scale area potential such as rural spatial planning, Kaligentong Village uses area mapping as an effort in village development planning. The mapping is displayed in paper media which has limited access so that this is inefficient and hinders the Kaligentong Village government in managing the assets and potential contained in it. Therefore, an information system is needed that can monitor the assets and potential of Kaligentong Village in the form of web-based digital maps and android. This study aims to create a dynamic digital mapping of villages for Kaligentong Village so that it is more efficient in finding and managing information related to geographical conditions and potential of Kaligentong Village. The method used is waterfall which consists of the stages of analysis, planning, modeling, construction, and testing. The system is built using javascript leaflets, native PHP, QGIS, and MySQL databases. Based on data from black box testing, the village digital map application runs according to the functional system. The satisfaction rate of application and web users is 94.10%. The average response time per activity generated by the application was 1.44s at 96 Mbps bandwidth and 0.89s at 144 Mbps bandwidth for websites.